The Role of Competence, Culture, and Socio-spiritual Factors in the Implementation of the Village Financial System - Diah Ekaningtias (The Indonesian Accounting Review, 2022)
This study aims to interpret how competence, culture, and socio-spiritual factors influence the implementation of the village financial system in Tanjungarum Village, Sukorejo, Pasuruan. This research is a case study using qualitative research method. The village head, village secretary, finance chief, and village treasurer were selected as the key informants. The results of this study reveal that the competency of village officials, as village government accountants, is still inadequate and it requires regular mentoring and training on operationalizing the village financial system. The cultural dimension inherent in the Tanjungarum Village community tends to be uniform, masculine and high power distance and it is an obstacle in accepting the new village financial system. The beginning of its implementation, the system experienced a lot of resistance, but in the end a culture of mutual help and acceptance of change was shown by the community. Strong socio-spiritual aspect also strengthens the formation of the character of Tanjungarum Village officials who are honest and religious so that they realize that life is a form of worship to God Almighty. Life is not merely for the sake of economic gain but more than that, it has an altruistic transcendental value that better prepares provisions for realizing transparent and accountable management of village funds.